Verbal mood in descriptions of denials of facts - Marques, Rui (2023)
The meaning of sentences that express the refusal of a fact involves two propositions: a complement clause that describes a fact, and the matrix proposition, that expresses the non-acceptance of the truth of the embedded proposition. In Portuguese, the mood that occurs in the complement clause is not the same in all constructions that convey this meaning. In some constructions, although there is an alternation between Indicative and Subjunctive in the complement clause, only with Indicative the interpretation that this proposition describes a fact of reality is observed. In other constructions, the mood of the complement clause is a matter of lexical selection, no alternation of mood being observed. Some factive predicates rule the Indicative, others rule the Subjunctive. In all these constructions the mood of the complement clause is explainable by mood analyzes in Portuguese available in the literature. However, there are two types of construction in Portuguese that express the refusal of the fact described by the complement clause and in which the mood of this clause is the opposite of the expected one. This text proposes a description of the meaning of these constructions, as well as an analysis of the Indicative and Subjunctive moods in Portuguese that explains in an integrated way the mood observed in all these constructions that express an attitude of rejection of the fact described by the complement clause.